2006
DOI: 10.1118/1.2402585
|View full text |Cite
|
Sign up to set email alerts
|

Robust experiment design for estimating myocardial adrenergic receptor concentration using PET

Abstract: Myocardial beta adrenergic receptor (beta-AR) concentration can substantially decrease in congestive heart failure and significantly increase in chronic volume overload, such as in severe aortic valve regurgitation. Positron emission tomography (PET) with an appropriate ligand-receptor model can be used for noninvasive estimation of myocardial beta-AR concentration in vivo. An optimal design of the experiment protocol, however, is needed for sufficiently precise estimates of beta-AR concentration in a heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Experimental designs were investigated for 2-and 3-injection studies to select the amount of unlabeled mefway and the injection time for each administration. The experimental design was selected using the D-optimal criterion, which minimizes the correlation between the kinetic parameters (described in Salinas et al, 2007). The inverse determinant of the reduced Hessian (det(H R ) À1 ) is proportional to the volume of the indifference region for the parameter estimates.…”
Section: Design Of the Multiple-injection Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental designs were investigated for 2-and 3-injection studies to select the amount of unlabeled mefway and the injection time for each administration. The experimental design was selected using the D-optimal criterion, which minimizes the correlation between the kinetic parameters (described in Salinas et al, 2007). The inverse determinant of the reduced Hessian (det(H R ) À1 ) is proportional to the volume of the indifference region for the parameter estimates.…”
Section: Design Of the Multiple-injection Experimentsmentioning
confidence: 99%
“…The requirement was enforced that the first injection of each study consist of high specific activity [ 18 F]mefway and 90 minutes of scanning. It has been shown that for other applications, it is possible to measure B max with a 2-injection protocol with partial saturating doses of the ligand for the first injection (Salinas et al, 2007). Such a design foregoes the ability to measure BP ND for comparison with radiotracer-only scans and was therefore not investigated for this work.…”
Section: Considerations In Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The D-optimal criterion, described in detail by Salinas and co-workers, 15 was used to maximize the identification and precision of the kinetic parameters B max , k on , and k off to select the optimal MI experimental design. Optimization of MI experiments focused on the thalamic regions of the brain.…”
Section: Experimental Designmentioning
confidence: 99%
“…2 For example multiple injection (MI) protocols using different specific activities (SA) were first proposed by Delforge et al 3 and subsequently used to estimate the affinity of labeled compounds, for example, CFT, 4 fallypride, 5 and fluorocarazolol. 6 Further, if a reference region devoid of specific target sites exists, the pseudoequilibrium method or multiple ligand concentration receptor assay can be applied using different SA injections, allowing for estimation of the affinity in an analogous manner to the in vitro Scatchard approach. 7,8 These methods work by achieving different levels of target occupancy via homologous competition with the radiolabeled compound, allowing separate estimates of target density and radioligand affinity.…”
Section: Introductionmentioning
confidence: 99%